Long-term determinants of portuguese public expenditures - Mourão, Paulo (2007)
This work aims at identifying the determinants that explain the growth of Portuguese public expenditures since the end of II World War. For the Portuguese reality, it is one of the first attempts to discuss a large set of simultaneously tested determinants. For this purpose, the methodology started from a model that tries to identify public expenditures to a system of simultaneous macroeconomic forces and, for testing, it followed the steps associated to the cointegration analysis. Using the most convenient techniques, a restrictive set of four variables (Number of Unemployed People, Number of Public Employees, Rate of Openness and Current Transfers per capita) was found among the wider set suggested by the Literature. The variable associated to the dominant force is the Number of Unemployed, whose percentual increase promotes a raise of almost 0,30% of Portuguese real total expenditures.